2019
DOI: 10.1007/s10694-019-00935-4
|View full text |Cite
|
Sign up to set email alerts
|

Opposed-Flow Flame Spread and Extinction in Electric Wires: The Effects of Gravity, External Radiant Heat Flux, and Wire Characteristics on Wire Flammability

Abstract: Combustion of electric wires is the most probable cause of fire in human space activities. Therefore, the fire performance of electric wires in microgravity conditions must be thoroughly analyzed. This study investigates the opposed-flow flame spread and its limits in electric wires preheated by external radiation, under both normal gravity and microgravity, to understand their fire performance when exposed to external heat sources in such gravity conditions. The experiments were performed on low-density polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Several previous studies have investigated the effect of these parameters on wire burning, including various wire characteristics [6]- [9], environmental conditions [6], [10]- [17], and geometries [8], [18], [19]; however, there are only a limited number of studies examining the effect of ambient pressure, specifically sub-atmospheric, on flame spread [15], [19]- [22]. This research is important because it has previously been found that low pressure environments can approximately mimic results found in micro-gravity environments [16], [17], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have investigated the effect of these parameters on wire burning, including various wire characteristics [6]- [9], environmental conditions [6], [10]- [17], and geometries [8], [18], [19]; however, there are only a limited number of studies examining the effect of ambient pressure, specifically sub-atmospheric, on flame spread [15], [19]- [22]. This research is important because it has previously been found that low pressure environments can approximately mimic results found in micro-gravity environments [16], [17], [21].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The one-side blowoff always occurred in the narrow strip fabrics with an adequate flame length, which was explained as the small Damköhler number caused by self-induced buoyant flow. The blow-off mechanism of a spreading flame has been widely investigated under downward or opposed force flow configurations [27][28][29][30][31][32] ; while a few findings of blow-off in upward spread flames in air stream due to limitation of sample length. Alternatives are used with an adjustable concurrent force flow to reduce the ratio of chemical time and residence time.…”
mentioning
confidence: 99%
“…Unique space fire experiments have been conducted in the International Space Station [5,6], unmanned spacecraft [7], and a satellite [8] to understand the long-term micro-gravity combustion and fire phenomena. The fire dynamics small and thin fuels are also explored through ground-based microgravity experiments using drop towers [9] and parabolic flights [10][11][12][13][14]. In addition, combustion and fire experiments under reduced pressures [15][16][17] and a narrow channel [18] are applied to lower the influence of buoyancy and simulate low-gravity environments on Earth.…”
mentioning
confidence: 99%
“…Proper material selection for spaceflight requires a thorough knowledge of fire and flammability behavior in varied gravity. Thus, the critical conditions for flame ignition and extinction in microgravity are extensively explored under different ignition protocols [12], oxygen concentrations [11][12][13], airflow rates [13] and radiant heat fluxes [11], and for flame retardant materials [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation